An approach to the determination of winter chill requirements for different Ribes cultivars. (18th April 2012) - Jones, H. G.; Hillis, R. M.; Gordon, S. L.; Brennan, R. M.
Abstract: Winter chilling is critical for flowering and fruiting of many temperate fruits, with evidence that blackcurrant ( Ribes nigrum L.) cropping has been adversely affected by warm winters. Accurate models of chill accumulation in blackcurrant are required so that breeding strategies can be formulated for the generation of new cultivars with resilience to future climates. Existing models for chill accumulation have largely been derived from statistical correlation; here we report the derivation of improved models for blackcurrant using controlled environment treatments. Hardwood cuttings from a diverse set of cultivars were exposed to constant or varying chilling temperatures and the effects on bud break after transfer to a warm, permissive environment evaluated. The impact of different combinations of temperature and chilling periods were described in terms of their overall 'Effectiveness' ( E ). Clear genotypic differences were found, with excessive chilling often inhibiting bud break. There was a significant interaction between observed chilling response and the period of low temperature exposure. A number of chilling models to explain observed interactions between chilling temperature and time of exposure on bud break were compared; the most effective involved an optimal response to increasing chill accumulation. The effects of varying temperatures during chilling on bud break were complex, with warm temperature breaks substantially inhibiting bud development and cooler temperature breaks tending to enhance bud burst. The relevance of these models to generic studies of endodormancy is discussed, together with their potential application to the development of phenotyping screens for future breeding using diverse blackcurrant germplasm.